Effect of subsequent pregnancies on HIV disease progression among women in the Mulago Hospital MTCT‐Plus program in Uganda. Issue 3 (31st December 2015) - Amongin, Dinah; Nakimuli, Annettee; Busingye, Robert; Mubiru, Mike; Musoke, Philippa; Mutyaba, Twaha
Abstract: Objective: To investigate the effect of subsequent pregnancies on HIV disease progression among HIV‐infected women at Mulago Hospital, Uganda. Methods: In a retrospective cohort study, data were analyzed from women enrolled in the Mother‐To‐Child Transmission Plus program from March 2003 to December 2011. The CD4 cell count, the development of new AIDS‐defining opportunistic infections, and the AIDS‐related mortality were compared between women with and without subsequent pregnancies. Results: Overall, 409 women were enrolled and 195 (47.7%) had subsequent pregnancies. Antiretroviral therapy (ART) was initiated in 143 (73.3%) women with and 155 (72.4%) women without subsequent pregnancies. Kaplan–Meier analysis for women receiving ART showed no differences between women with and without subsequent pregnancies in the median times to clinical failure (62.7 vs 64.7 months; P = 0.31), immunological failure (68.8 vs 75.5 months; P = 0.10), and death (68.8 vs 75.5 months; P = 0.53). In a Cox regression analysis, subsequent pregnancies were not associated with immunological failure during follow‐up (adjusted hazard ratio 1.13, 95% confidence interval 0.06–2.09). Conclusion: Subsequent pregnancies could have no detrimental effect on HIV disease progression among HIV‐infected women whose treatment is well managed.